The Sound of a Monumental Architecture - Fratoni, Giulia (Canadian Acoustics, 2020)
The present work is intended to be a scientific commentary on the ``''SynAsTex Korrektur'' sound performance by the German artist Florian Hecker. The choice of the venue for the performance fell on the rationalist atrium of the School of Engineering of the University of Bologna, which is part of a historical building dating back to the 1930s. The study tries to answer some questions. Which role can be played by the acoustics of a monumental atrium - which is made by marble and reflective surfaces - in an electronic performance? How much may the presence of the standing audience influence the room acoustics? Which are the peculiarities of the sound energy distribution in this kind of strongly non-diffuse sound field? The assessment of the acoustic condition was carried out through acoustic simulations, employing a ray-based approach.